In vitro evaluation of root canal preparation using oscillatory and rotary systems in flattened root canals - Rasquin, Luis Cardoso; de Carvalho, Fabiola Bastos; de Pontes Lima, Regina Karla [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2007)
Objective: the aim of this study was to evaluate the biomechanical preparation of flattened root canals using the following systems: Endo-Eze AET stainless steel oscillatory instruments (Ultradent) and RaCe rotary NiTi instruments (FKG Dentaire). Materials and Methods: Twenty extracted human mandibular incisors were randomly assigned to two groups: Group I Instrumentation with oscillatory Endo-Eze AET files (oscillatory technique); Group 2 - Instrumentation with rotary NiTi RaCe files (rotary technique). The teeth were decoronated, had their apices and coronal openings sealed with sticky wax and were embedded in crystal-clear orthophtalic polyester resin. The roots were sectioned transversally with diamond discs at 10 mm (middle third) and 5 mm (apical third) from the apex and the segments were reassembled for instrumentation. The sections were photographed before and after root canal instrumentation and evaluated with respect to whether the original root canal shape was modified by instrumentation. To evaluate the differences in the root canal shape before and after biomechanical preparation, scores were given regarding the instruments touch on the intracanal walls. Results: In middle third of the root canals instrumented with the rotary system, there was a change in the original canal anatomy (p < 0.05), with formation of a protuberance in the mesiodistal direction. This protuberance did not occur when the oscillatory instrumentation was used. The oscillatory system had better results in the middle and apical thirds as evaluated by Dunn's multiple-comparison test (p > 0.05). Conclusion: Under the tested conditions, Endo-Eze oscillatory system yielded the instrumentation of all flattened oot canal walls, maintaining the canal original shape throughout the biomechanical preparation, and was more effective than RaCe rotary system.
Keywords: flattened root canal; root canal preparation; oscillatory systems; rotary systems